A SCIENTOMETRIC ANALYSIS IN ISLAMIC EQUITY MARKET: WHERE SHALL WE GO? - Firmansyah, Muhamad Ferdy (UNISSULA, 2022)
This study aims to determine the development and development of research trends in the published Islamic equity market and to shape research streams. The data used in this study were 449 scientific articles published in the period 1986-2021. The data sources used are scientific journals indexed on Dimension.ai using the search keyword